Progress on characteristics and application of yeasts and its derivatives in fruit wine brewing - FENG Jun, FENG Xiaohong, LI Ke, TIAN Xinhui, YUAN Jie, ZHAO Xingtong, HE Junyao, LIU Yao (Zhongguo niangzao)
Yeast and its derivatives play a key role in the production of fruit wine. Both of Saccharomyces cerevisiae and non-Saccharomyces participate in brewing and determine the style and quality of fruit wine through different metabolic pathways. The yeast derivatives can enhance the yeast vitality and fermentation efficiency in the fermentation stage of fruit wine, promote the coordination of the wine body and improve sensory quality in the post-fermentation stage. Therefore, yeast and its derivatives have a natural and inseparable relationship in the brewing process of fruit wine. At present, the synergistic application of yeast and its derivatives in fruit wine brewing is mainly concentrated on wine, and systematic research on other fruit wines is still rarely reported. In this paper, the types, characteristics, functions and applications of commercial S. cerevisiae and non-Saccharomyces used in fruit wine brewing were reviewed, the brewing characteristics and functions of yeast derivatives were introduced, aiming to provide theoretical basis for the high-quality development of China's fruit wine industry.